Nursing Role with Incident Command System in Disaster - สิริภักดีกาญจน์, ชญาลักษณ์ (Journal of The Royal Thai Army Nurses, 2018)
The Incident Command System (ICS) is the tool that used in disaster management for command, control, and coordination of the response and provides a means to coordinate the efforts of individual agencies as they work toward the common goal of stabilizing the incident and protecting life, property, and the environment. The ICS organization is built around two major components including Command and General Staff. General Staff part have 5 sections consisting 1) Operation section 2) Planning section 3) Intel/Investigation section 4) Logistic section and 5) Finance/Administration section. Nurses are among the largest in the health service system. They should have a thorough understanding of the Incident Command System, role as assigned, incident organization and coordinating guideline to work within emergency situations under pressure with smoothly, flexible, and systematic working. Furthermore, they should be understand, policies and practices guideline of the agency for making the operation in the same direction. As a result, the health services in helping the victims will be effective, fast, and safe to response the needs of victims, reduce the severity of injury and loss of life of victims.